2010
DOI: 10.1166/jnn.2010.2856
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Photoluminescence and Wettability Properties of Well Arrayed ZnO Nanowires Grown by Hydrothermal Method

Abstract: Well aligned ZnO nanowire arrays with high crystal quality were grown on Si substrates at a low temperature (50 degrees C) by hydrothermal method using a pre-formed ZnO seed layer. ZnO seeds were prepared via radio-frequency magnetron sputtering onto Si substrates. The morphologies of the ZnO nanowire arrays were shown by field emission scanning electron microscopy. X-ray diffraction spectra showed that the full width at the half maximum of the (0002) peak of the nanowire arrays without any heat treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The ZnO has advantages over the porous TiO 2 , such as higher electron diffusivity, a higher electron mobility, is available at low-cost, and stability against photocorrosion [11,12]. In addition, the polar surfaces of the wurtzite crystalline structure enables the growth of many kinds of ZnO nanostructures [13], including nanowires [14], nanorods [15], nanobelts [16], nanosprings [17], nanorings [18], nanobowls [19], nanoflowers [20], and nanohelices [21]. Among all these structures, in particular, the one dimensional (1-D) ZnO nanostructures, like as nanorods and nanowires, have received increasing attention in recent years, due to its excellent physical and chemical properties, which can provide an effective direct pathway for rapid transport of the photoelectrons and a higher surface area for dye adsorption, enhancing the photovoltaic performance of the DSSCs [22e24].…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO has advantages over the porous TiO 2 , such as higher electron diffusivity, a higher electron mobility, is available at low-cost, and stability against photocorrosion [11,12]. In addition, the polar surfaces of the wurtzite crystalline structure enables the growth of many kinds of ZnO nanostructures [13], including nanowires [14], nanorods [15], nanobelts [16], nanosprings [17], nanorings [18], nanobowls [19], nanoflowers [20], and nanohelices [21]. Among all these structures, in particular, the one dimensional (1-D) ZnO nanostructures, like as nanorods and nanowires, have received increasing attention in recent years, due to its excellent physical and chemical properties, which can provide an effective direct pathway for rapid transport of the photoelectrons and a higher surface area for dye adsorption, enhancing the photovoltaic performance of the DSSCs [22e24].…”
Section: Introductionmentioning
confidence: 99%
“…Well aligned ZnO nanowire arrays grown on Si substrates by hydrothermal method also presented superhydrophobic with a contact angle of about 165 • when they are modified via low surface energy materials such as long chain fluorinated organic compounds [23]. The excellent water repellent properties of quasi-aligned ZnO nanowire arrays coated with an octadecyltrichlorosilane (OTS) monolayer was reported by Sarkar et al [24]. While some people have found that by controlling the surface nanostructure, the wettability of films with similar pore-array microstructure can be tuned from hydrophilic to nearly superhydrophobic without variation of the chemical composition [25].…”
Section: Introductionmentioning
confidence: 81%
“…While surface roughness is well known to contribute to water-repellency, quantitative analysis of this phenomenon is usually imprecise due to imperfection of the surface structure. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] With precisely controllable geometries, the asprepared SiNR arrays are well suited for such analysis. Therefore, as an add-on, we further investigated the hydrophobicity of the as-prepared SiNR arrays.…”
mentioning
confidence: 99%